2016
DOI: 10.1098/rstb.2015.0044
|View full text |Cite
|
Sign up to set email alerts
|

A flexible genetic toolkit for arthropod neurogenesis

Abstract: One contribution of 16 to a discussion meeting issue 'Homology and convergence in nervous system evolution'. Arthropods show considerable variations in early neurogenesis. This includes the pattern of specification, division and movement of neural precursors and progenitors. In all metazoans with nervous systems, including arthropods, conserved genes regulate neurogenesis, which raises the question of how the various morphological mechanisms have emerged and how the same genetic toolkit might generate differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 103 publications
(160 reference statements)
0
22
0
Order By: Relevance
“…Chelicerata and Myriapoda have been less frequently studied and seem to display a remarkably different pattern of immunoreacticity than Tetraconata (Washington et al, 1994 ;Harzsch, 2004;Brenneis and Scholtz, 2015). Furthermore, Chelicerata and Myriapoda differ substantially in the mode of neurogenesis compared with Crustacea and Hexapoda (reviewed in Stollewerk, 2008Stollewerk, , 2016, supporting the Tetraconata concept (discussed in detail by Harzsch et al, 2005). Thus, the following considerations will focus on Tetraconata.…”
Section: Comparison Of Serotonin-immunoreactive Neurons In the Vnc Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Chelicerata and Myriapoda have been less frequently studied and seem to display a remarkably different pattern of immunoreacticity than Tetraconata (Washington et al, 1994 ;Harzsch, 2004;Brenneis and Scholtz, 2015). Furthermore, Chelicerata and Myriapoda differ substantially in the mode of neurogenesis compared with Crustacea and Hexapoda (reviewed in Stollewerk, 2008Stollewerk, , 2016, supporting the Tetraconata concept (discussed in detail by Harzsch et al, 2005). Thus, the following considerations will focus on Tetraconata.…”
Section: Comparison Of Serotonin-immunoreactive Neurons In the Vnc Ofmentioning
confidence: 99%
“…However, a caveat toward an approach that considers cellular homologies between arthropod taxa based on common developmental origin (Thomas et al, ) came from studies that showed different morphological mechanisms for neurogenesis among arthropods (Dohle and Scholtz, ; reviewed in Stollewerk, ). Whereas insect neuroblasts delaminate from the ventral neuroectoderm, crustacean neuroblasts remain in the ventralmost cell layer (reviewed in Stollewerk, ). This called into question whether neuroblasts in insects are homologous to neuroblasts in crustaceans (Dohle and Scholtz, ; Scholtz, ).…”
mentioning
confidence: 99%
“…Many aspects of cellular and genetic bases of neural development are conserved in animals (Denes et al 2007 ; Hartenstein and Stollewerk 2015 ). In particular, the gene networks involved in specifying neural precursors and their spatial identity are highly conserved in insects and partly even in other arthropods (Wheeler et al 2005 ; Stollewerk and Simpson 2005 ; Eriksson and Stollewerk 2010 ; Biffar and Stollewerk 2014 ; Stollewerk 2016 ). Homology of neural lineages has been suggested based on Crustacean neuroblasts, which show a comparable spatial arrangement, timing of delamination, transcription factor expression, and projection patterns as their insect counterparts (Ungerer and Scholtz 2008 ).…”
Section: Diversity Of Adult Brain Morphology and Developmental Timingmentioning
confidence: 99%
“…The genes controlling neurogenesis are highly conserved across animals [42] and development of key structures such as the cerebellum in vertebrates is increasingly well understood [43]. By contrast, there are few examples where a direct link between genes and specific behaviours have been demonstrated (see [44] for a review).…”
Section: Variation In Ability Technique and Skill (A) Variation In Amentioning
confidence: 99%